(untitled) (Nordic Journal of African Studies, 2005)
This study attempts to identify and discuss writing problems in Kiswahili in Tanzanian secondary schools. The study uses data from two schools specifically selected as case studies. The study submits that pedagogically, unlike speaking which is acquired without explicit instructions, writing as a skill has to be taught. Failure to appreciate this difference leads to communicative writing problems. The present study reveals six glaring writing problems, namely: capitalization and punctuation problems, inexplicitness or fuzziness, poor organization or illogical sequence, spelling problems and grammatical errors. The study argues that most of these writing problems arise from pedagogical reasons. To a greater extent, these problems are not limited only to the two schools involved in the study, but apply also to other schools and higher learning institutions as well. Thus, the study advocates that writing problems can be minimized if the students are taught writing as a skill by professional Kiswahili language teachers.